Número mínimo de indivíduos e diversidade genética de Onça-parda (Puma concolor) no Núcleo Santa Virgínia, Parque Estadual da Serra do Mar, São Paulo - Martins, Niara (2011)
ABSTRACT The cougar (Puma concolor) is the second largest feline species in Brazil. It has a wide distribution across the Americas, occurring from southwestern Canada to the Strait of Magellan, in the extreme south of Argentina and Chile, throughout the Brazilian territory. In this study we estimated the minimum number of individuals and genetic diversity of cougars in the Santa Virginia Unit, Serra do Mar State Park (PESM), São Paulo, based on fecal DNA analysis. Hair snares were also used to an attempt to obtain more samples. For the diagnosis of the species, we amplified a 146bp fragment of the cytochrome b gene of mitochondrial DNA. We used six microsatellite loci for the fecal samples individualization, to estimate the minimum number of individuals and genetic characterization of the population. No hair sample was obtained during the study. Among the 40 fecal samples obtained, 34 were successfully diagnosed, and we found 25 samples of P. concolor, eight of Leopardus tigrinus and one of Leopardus pardalis. The multiloci genotypes were obtained for only 15 samples belonging to 12 different puma individuals. The allelic dropout average rate was 10.43%. The mean observed heterozygosity was 0.6202, lower than that found for the species in fragmented areas of Cerrado, in the northeastern São Paulo. There were deviations in Hardy-Weinberg equilibrium (HWE) for one locus and a deficit of heterozygous for the set loci used. However, there was no evidence of recent population bottleneck. Therefore, the deviation in HWE could be caused by the presence of null alleles or the low number of samples. Little relationship was found between individuals (6.1% Half-Sibs), indicating a possible continuous stream of cougars in the region. Thus, the PESM deserves special attention for being the largest continuous remnant of Brazilian Atlantic Forest and, therefore, similar studies are needed in the others Units of this Park so that together they can provide a more comprehensive view of the P. concolor situation in this biome.